Generasi Hemat Atau Generasi Terpaksa? Potret Anak Muda Bertahan di Tengah Inflasi - Eza Olivia; Deta Elisa; Nuzulla Aurora Brilian; M.Yusuf Bahtiar (Kajian Ekonomi dan Akuntansi Terapan, 2026)
This study exaimines whether today’s youth represent a “saving generation” or a “forced generation” in respondingto rising inflation.the increasing cost of living has significantly affected young people’s consumption patterns,financial planning,and lifestyle choices.this researchaims to analyze how inflation influences the economic behavior of young people and to identify whether their frugality is driven by financial awereness or economic pressure.the study employs a qualitative descrective approach,using interviews and literature analysis to explore the experience of young individuals in managing their finances amid economic uncertainty.the findings indicate that although some young people demosntrate improved financial literacy and budgeting skills,many are compelled to reduce concumption,postpone personal goals,and limit social activities due to limited income and rising prices.Inflation has reshaped priorites,encouraging survival-oriented financial strategies rather than long-term wealth planning.the study concludes that the current generation reflects a combination of both conscious constraint.therefore,policy interventions,financial educations programs,and employment opportunities are essential to strengthen youth economic resilience.the implications of supporting young people in  developing sustainable financial habits while addressing structural economic challenges that influence their financial stability.